Actigraph Evaluation of Acupuncture for Treating Restless Legs Syndrome. (11th February 2015) - Pan, Weidong; Wang, Mingzhe; Li, Mao; Wang, Qiudong; Kwak, Shin; Jiang, Wenfei; Yamamoto, Yoshiharu
Abstract : We evaluated the effects of acupuncture in patients with restless legs syndrome (RLS) by actigraph recordings. Among the 38 patients with RLS enrolled, 31 (M = 12, F = 19 ; mean age, 47.2 ± 9.7 years old) completed the study. Patients were treated with either standard acupuncturen = 15 or randomized acupuncturen = 16 in a single-blind manner for 6 weeks. Changes in nocturnal activity (NA) and early sleep activity (ESA) between week 0 (baseline), week 2, week 4, and week 6 were assessed using leg actigraph recordings, the International Restless Legs Syndrome Rating Scale (IRLSRS), and Epworth Sleepiness Scale (ESS). Standard but not randomized acupuncture reduced the abnormal leg activity of NA and ESA significantly in week 2, week 4, and week 6 based on the changes in the clinical scores for IRLSRS and ESS in week 4 and week 6 compared with the baseline. No side effects were observed. The results indicate that standard acupuncture might improve the abnormal leg activity in RLS patients and thus is a potentially suitable integrative treatment for long-term use.